Influence of different planting techniques and cutting practices on chlorophyll content index and nutrient uptake by barley (Hordeum vulgare L.) - Lal, Manohar; Saini, K.S. (Annals of Agricultural Research, 2016)
A field study was conducted to assess the effect of different planting techniques and cutting practiceson chlorophyll content index and nutrient uptake by barley (Hordeum vulgare L.) during the rabiseason of 2014-15 at Student's Research Farm, Punjab Agricultural University, Ludhiana. The soil ofexperimental field was moderately alkaline (8.3) to strongly alkaline (8.8). The experiment was laidout in randomized block design (RBD) with 9 treatments having three planting techniques viz.unidirectional (UD), bidirectional (BD), broadcasting (BC) and three cutting practices viz. uncut(UNC), cut at 50 DAS (C50 DAS) and cut at 60 DAS (C60 DAS) with four replications. The chlorophyllcontent index at 50 and 90 DAS was significantly higher in bidirectional planting techniques anduncut than other treatments. The N, P and K content (grain and straw) and uptake under bidirectionalplanting techniques were higher than broadcasting and unidirectional planting techniques. Thecutting practices in uncut treatment recorded significantly higher CCI, N, P and K content anduptake than C50 DAS and C60 DAS of barley. The bidirectional planting techniques and uncuttreatment recorded significantly higher protein yield than other treatments of dual purpose barley.Partial nutrient balance (PNB) under bidirectional planting technique and uncut were significantlyhigher than other treatments. Nutrient efficiency ratio (NER) was significantly better in uncuttreatment compared to other treatments.